Reliability process methodology of the centrifugal rotary machining in the medium of steel balls - Denis Vladimirovich Kazakov (Advanced Engineering Research)
The research results on improving reliability of the finishing-strengthening centrifugal rotary processing are presented. The research subject is the formation of the finishing and strengthening centrifugal rotary processing (FS CRP) reliability provided by a reasonable coupling of the technological modes and operating environment characteristics. The research objective is to improve efficiency and reliability of the finishing-hardening centrifugal rotary processing with studying the arising failures based on the development of a set of the adequate theoretical processing patterns. The refined theoretical patterns of the finished part surface layer indices forming - the extent and depth of hardening, are obtained. The analytical forecasting methodology of the finishing-hardening centrifugal rotary processing reliability with the following parameters: the coefficient of the instantaneous scattering of the controlled variable, the offset coefficient of the controlled variable, and the coefficient of the process marginal accuracy, is developed. It is established that the FS CRP process provides obtaining the required parameters of the workpiece surface quality under the processing within the tolerance values in a certain range of the technological mode change and the operating environment characteristics. The design technique for the FS CRP processes with allowance for their reliability is developed.